2022
DOI: 10.15406/paij.2022.06.00264
|View full text |Cite
|
Sign up to set email alerts
|

On radiation protection and climate change – a summary

Abstract: planned for construction as well as those at proposal stage. However, the ethics of nuclear power is increasingly under challenge due to the incidents at the Chernobyl and Fukushima Daiichi nuclear power plants, and concerns over radioactive discharges, safe management of radioactive waste and lack of an operational repository for spent nuclear fuel. Central to these concerns is the perceived unique radiological risk of nuclear power. But in a world where Climate Change presents a threat to the entire planet, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…To determine the decay width Γ across different decay channels, one can employ the amplitude |M| and phase space integrals, as outlined by. 9 The calculation of the decay width proceeds as follows:…”
Section: F Decay Width Calculationsmentioning
confidence: 99%
“…To determine the decay width Γ across different decay channels, one can employ the amplitude |M| and phase space integrals, as outlined by. 9 The calculation of the decay width proceeds as follows:…”
Section: F Decay Width Calculationsmentioning
confidence: 99%
“…In Quantum mechanics, scattering involves alterations in particle trajectories or states during interaction essential for understanding phenomena like particle accelerations and light scattering by atoms. 7,8 At the core of this theory is the scattering amplitude, depicting the transition probability from an initial to a final state. Various theoretical frameworks and mathematical tools like the Born approximation and partial wave analysis facilitate the study of quantum scattering.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Quantum scattering plays a pivotal role in various fields of physics, chemistry, and even beyond, influencing areas such as materials science, quantum computing, and nuclear physics among others. 3,4 Theoretical concepts such as the Schrödinger equation, scattering amplitude, and scattering cross-section are highlighted in this, along with their significance in describing particle interactions with potential energy fields. 5,6…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 This has made researchers to conclude that there should be a relationship between variations of solar radiation from the sun and global climate change. 4 These phenomena, including unsafe human activities, could be the reason we are facing a relatively sharp global temperature rise. 5 The past years have shown that the sun has contributed significantly in the changes that our climate is facing today.…”
Section: Introductionmentioning
confidence: 99%